Methods of studying science schools in the history of the ukrainian human geography - Олійник, Ярослав; Шевчук, Сергій (Human Geography Journal, 2016)
In this article the relevance and indicated the difficulty of teaching the history of Ukrainian studies in human geography. On the basis of the main tasks, areas of research in the history of the geography of the classification methods for studying the history of the Ukrainian community of geography as an example of scientific schools. A system of such research methods and justified the use of each in the context of studying the formation and development of scientific schools in the Ukrainian community of geography.